Comparative evaluation of different soybean meal and the replacement using peanut, rapeseed and fish meal for broilers . - Tangendjaja, Budi; Bintang, I.A.K (Indonesian Animal Sciences Society, 1996)
Two feeding experiments have been conducted to test the different sources of soybean meal (local, India, USA) and the partial substitution with peanut meal (10%), rapeseed meal (5%) and fish meal (5%) in the diet for broiler. The first feeding experiment was carried out on broiler starter for 4 weeks in wire cages . Twelve rations in factorial design (3 x 4) were conducted using 6 birds/cage and replicated 6 times . Birds fed India soybean meal had significantly less body weight (1,000 g) than those fed local or USA soybean meals (1,037 and 1,023 g, respectively) . Partial substitution with peanut, rapeseed or fish meal did not affect body weight, feed consumption or feed/gain ratio . The average consumption and feed/gain were 1,535 g and 1,569, respectively . In second experiment, one thousand five hundred broiler chicks were allocated in 6 dietary treatments in factorial design (3 x 2) . Factor one was different sources of soybean meal (local, India and USA) and factor two was the inclusion of peanut meal at 0 and 10%. Birds were kept on litter system for 6 weeks . Each treatment used 5 replicates and 50 birds/replicate . The results show no effect of the treatment to any parameter measured . Body weight of bird fed local, India and USA soybean meal were 1,662, 1,641 and 1,669 g and feed/gain were 2 .043, 2 .051 and 2.035, respectively . Cost analysis indicates that ration uses local soybean meal gives a higher cost than those of India and USA soybean meals. Â Key words : Soybean meal, peanut meal, rapeseed meal, fish meal, broiler Â